A Single Institution Retrospective Study of the Clinical Efficacy of Tiotropium Respimat in Never-Smoking Elderly Asthmatics with Irreversible Airflow Limitation - Hara, Johsuke; Kasahara, Kazuo; Ohkura, Noriyuki; Yamamura, Kenta; Sakai, Tamami; Abo, Miki; Ogawa, Naohiko; Saeki, Keigo; Koba, Hayato; Watanabe, Satoshi; Uchida, Yuka; Tambo, Yuichi; Sone, Takashi; Kimura, Hideharu (Drug Research, 2019)
Objective In Japan, most asthma deaths occur among the elderly. We should improve the control of asthma in elderly patients to reduce the number of deaths due to asthma. This retrospective study aimed to evaluate the efficacy of tiotropium RespimatⓇ (Tio-Res) in symptomatic, never-smoking, elderly asthmatics with irreversible airflow limitation despite the use of high-dose inhaled corticosteroids (ICS) plus long-acting β2-adrenoceptor agonists (LABA).Methods The Asthma Control Test™ (ACT), pulmonary function tests, morning and evening peak flow (mPEF, ePEF, respectively, evaluated with an ASSESS® peak flow meter), and respiratory impedance (assessed with MostGraph®) were measured before and after a minimum of one year of Tio-Res 5 µg/day administration. Sixteen symptomatic, never-smoking asthmatics, aged 75 or over with irreversible airflow limitation despite the use of high-dose ICS plus LABA, were analyzed.Results All patients were female (mean age, 81.6 years). Tio-Res led to statistically significant improvements in the total ACT score (19.9 to 23.6), FVC and FEV1 (1.97 to 2.14 L and 1.13 to 1.23 L, respectively), and mPEF and ePEF (229.9 to 253.8 L/min and 259.8 to 277.4 L/min, respectively). Tio-Res also resulted in statistically significant improvements in respiratory resistance at 5 Hz (R5), respiratory resistance at 20 Hz (R20), R5-R20, low-frequency reactant indices at 5 Hz (X5), resonant frequency (Fres) and low-frequency reactance area (ALX).Conclusions Our retrospective study suggests that Tio-Res improves symptoms, pulmonary function, and respiratory impedance in symptomatic asthmatics aged 75 or over with irreversible airflow limitation despite the use of high-dose ICS plus LABA.
Keywords: Bronchial asthma; Irreversible airflow limitation; Never smoking; Multi-frequency oscillation technique; Tiotropium Respimat®